Risk Management of Life Insurance Companies in China - Yang, Yingru (2019)
As professional financial institutions that collect and disperse risks, insurance companies not only assume and transform the risks of the insured but also prevent and resolve themselves’ risks. So, risk management is particularly important for insurance companies. The concept of Enterprise Risk Management develops from risk management. Currently, ERM theory has been widely adopted by the large financial insurance companies in developed countries, which is of great significance in improving business value and abilities to prevent and handling risks.